Assessment of anti-psoriatic activity of ethanolic extract of Justicia tranquebariensis Linn. on amelioration of IMQ-induced hyperkeratosis in Balb/C mice - Divya Bharathi, Latha Subbiah, Prabha Thangavelu, Selvamani Palanisamy (Journal of Applied Pharmaceutical Science, 2020)
Psoriasis characterized by abnormal keratinocyte hyper proliferation results in the thickening of the epidermis and the stratum corneum. Anti-psoriasis treatments available today are poorly efficient, having many side effects, making them unsuitable for therapeutic use. Hence, the search for safer and more effective drugs from natural resources is necessarily warranted. In the present study, the leaves of Justicia tranquebariensis Linn. have been evaluated for its anti-psoriatic activity to substantiate the traditional claim as an anti-psoriatic agent scientifically. Additionally, an EJTL ointment was formulated for the in vivo anti-psoriatic evaluation in Balb/c mice together with its histopathological study. The obtained results revealed the presence of primary phytochemicals, such as flavonoids and lignans in the ethanol extract of the leaves of J. tranquebariensis L. (EJTL). Furthermore, the UV-Visible and Fourier Transform Infrared Spectrums confirmed the existence of the relevant functional groups supports the presence of Isolariciresinol in the EJTL ethanol extract. In vivo evaluation of the EJTL ointment showed the remarkable anti-psoriatic activity in Balb/c mice with imiquimod (IMQ) induced psoriasis-like inflammation. The histopathological study results revealed significant improvement in skin lesion when compared to the positive control group. The anti-psoriatic activity further confirmed by observing the prominently decreased lymphocyte and keratinocyte infiltration in the dermis. A brief phytochemical characterization showed the presence of the active botanical ingredient, Isolariciresinol, assumed to have the anti-psoriatic property. Furthermore, the EJTL could be a potential drug for psoriasis either individually or synergistically with other herbals or anti-psoriatic agents.
Keywords: Justicia tranquebariensis, anti-psoriatic effect, IMQ-induced psoriasis, isolariciresinol, histopathological study.